2019
DOI: 10.1002/ccd.28075
|View full text |Cite
|
Sign up to set email alerts
|

Personalized antiplatelet therapy in patients with coronary artery disease undergoing percutaneous coronary intervention: A network meta‐analysis of randomized clinical trials

Abstract: Objectives This study aimed to evaluate the efficacy and safety of genotype‐ and phenotype‐guided intensified antiplatelet therapy compared with conventional therapy in patients undergoing stent implantation. Background Although potent P2Y12 receptor inhibitors are recommended for percutaneous coronary intervention (PCI)‐treated acute coronary syndrome, their usage is limited by a high bleeding risk. Therefore, personalized antiplatelet therapy could provide a valuable foundation for selection of antiplatelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Pharmacogenetic detection has emerged in clinical practices to guide cardiovascular drug therapy over the past decade ( Duarte and Cavallari, 2021 ). There was increasing evidence from ACS that obtaining genotype data early after percutaneous coronary intervention for patients with CYP2C19 loss-of-function alleles, and thereby developing genotype-guided personalized antiplatelet therapeutic regimens could reduce the risk of major adverse cardiovascular events ( Cavallari et al, 2018 ; Kheiri et al, 2019 ). Thus, we conducted this genotype-guided antiplatelet therapy in ischemic stroke and TIA to evaluate its clinical values.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacogenetic detection has emerged in clinical practices to guide cardiovascular drug therapy over the past decade ( Duarte and Cavallari, 2021 ). There was increasing evidence from ACS that obtaining genotype data early after percutaneous coronary intervention for patients with CYP2C19 loss-of-function alleles, and thereby developing genotype-guided personalized antiplatelet therapeutic regimens could reduce the risk of major adverse cardiovascular events ( Cavallari et al, 2018 ; Kheiri et al, 2019 ). Thus, we conducted this genotype-guided antiplatelet therapy in ischemic stroke and TIA to evaluate its clinical values.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Several large meta-analyses showed that CYP2C19 genotype-guided strategies could reduce ischemic events in CAD patients, especially in patients undergoing PCI, compared to conventional therapy. [15][16][17][18] Pereira et al showed that the super ior ity of the more potent P2Y12 inhibitors, ticagrelor, and prasugrel, in CAD patients was based pr imar ily on CYP2C19 LOF-alleles since these treatment strategies significantly reduced ischemic events in CYP2C19 LOF-allele carriers, but not in non-carriers. 17 So far, no large-scale prospective research has been performed to investigate the clinical relevance of CYP2C19 LOF-alleles in PAD patients treated with clopidogrel, nor is there any trial evidence regarding the added value of CYP2C19 genotype-guided treatment.…”
Section: Introductionmentioning
confidence: 99%